2009
DOI: 10.1007/s00445-009-0306-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of magma chamber-fault interaction in caldera forming eruptions

Abstract: This paper examines the role of the position and orientation of a regional fault in the roof of a magma chamber on stress distribution, mechanical failure, and dyking using 2D finite element numerical simulations. The study pertains to the magma chamber behavior in the relatively short time intervals of several hundreds to thousand of years. The magma chamber is represented as an elliptical inclusion (eccentricity, a/b=0.12) at a relative depth, H/a, of 0.9. The fault has a 45°dip and is represented by a frict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 39 publications
(57 reference statements)
2
28
0
Order By: Relevance
“…Subsequent analysis of the interaction between magma batches and a rising dike often employs consideration of the principle stress (σ 1 ) directions around a magma reservoir, defi ning approximate trajectories for diking via hydraulic fracturing of rocks (Jellinek and DePaolo, 2003;Simakin and Ghassemi, 2010;Karlstrom et al, 2012). This analysis leads to the observation that for the overpressurized deep spherical magma reservoir (equally inelas-tic, viscoelastic, or viscous media), σ 1 directions are such that the greatest compressive stress is radial to the magma body and σ 3 is tangential (Fig.…”
Section: Formation Of Magma Sills and Batchesmentioning
confidence: 99%
See 3 more Smart Citations
“…Subsequent analysis of the interaction between magma batches and a rising dike often employs consideration of the principle stress (σ 1 ) directions around a magma reservoir, defi ning approximate trajectories for diking via hydraulic fracturing of rocks (Jellinek and DePaolo, 2003;Simakin and Ghassemi, 2010;Karlstrom et al, 2012). This analysis leads to the observation that for the overpressurized deep spherical magma reservoir (equally inelas-tic, viscoelastic, or viscous media), σ 1 directions are such that the greatest compressive stress is radial to the magma body and σ 3 is tangential (Fig.…”
Section: Formation Of Magma Sills and Batchesmentioning
confidence: 99%
“…Pressure lower than lithostatic may develop in a magma body with a low supply fl ux during the solidifi cation of magma due to the volume effect of crystallization and escape of exsolved fl uid phases, and due to extensional tectonics. Numerical simulations of viscoelastic elliptic chambers (see Simakin and Ghassemi, 2010) demonstrated that at magma pressures lower than lithostatic pressures, expressed through the bottom-parallel σ 1 stress directions, the rock envelope presses into the chamber and undergoes radial extension. These arguments support accumulation of newly arriving batches of magma into a single growing magma body in sites of active magma generation and high intrusion rate.…”
Section: Formation Of Magma Sills and Batchesmentioning
confidence: 99%
See 2 more Smart Citations
“…Grouping of dikes in certain directions is less dependent on the magma chamber overpressure and is controlled by regional tectonic stresses (Nakamura, 1977;Acocella and Neri, 2009). The size and configuration of volcanic edifice and magma reservoir, and the edifice load also may have effect on the direction of the dike emplacement (e.g., Pinel and Jaupart, 2003;Simakin and Chassemi, 2009). Fig.…”
Section: The Position Of Dikes In the Old Shiveluch Edifice And Prerementioning
confidence: 99%